Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Solve the system of inequalities:

[tex]\[
\begin{array}{l}
y \ \textgreater \ -3x + 3 \\
y \geq 2x - 2
\end{array}
\][/tex]

Determine which of the following points satisfy both inequalities:
- (1, 0)
- (-1, 1)
- (2, 2)
- (0, 3)


Sagot :

Certainly! Let's analyze each of the points \((1,0)\), \((-1,1)\), \((2,2)\), and \((0,3)\) to determine if they satisfy both inequalities:
1. \( y > -3x + 3 \)
2. \( y \geq 2x - 2 \)

### Checking Point \((1, 0)\)
For the inequalities:
1. \( 0 > -3(1) + 3 \)
- Calculate the right side: \( -3(1) + 3 = -3 + 3 = 0 \)
- The inequality becomes \( 0 > 0 \), which is false.

2. \( 0 \geq 2(1) - 2 \)
- Calculate the right side: \( 2(1) - 2 = 2 - 2 = 0 \)
- The inequality becomes \( 0 \geq 0 \), which is true.

Since the first inequality is false, the point \((1, 0)\) does not satisfy both inequalities.

### Checking Point \((-1, 1)\)
For the inequalities:
1. \( 1 > -3(-1) + 3 \)
- Calculate the right side: \( -3(-1) + 3 = 3 + 3 = 6 \)
- The inequality becomes \( 1 > 6 \), which is false.

2. \( 1 \geq 2(-1) - 2 \)
- Calculate the right side: \( 2(-1) - 2 = -2 - 2 = -4 \)
- The inequality becomes \( 1 \geq -4 \), which is true.

Since the first inequality is false, the point \((-1, 1)\) does not satisfy both inequalities.

### Checking Point \((2, 2)\)
For the inequalities:
1. \( 2 > -3(2) + 3 \)
- Calculate the right side: \( -3(2) + 3 = -6 + 3 = -3 \)
- The inequality becomes \( 2 > -3 \), which is true.

2. \( 2 \geq 2(2) - 2 \)
- Calculate the right side: \( 2(2) - 2 = 4 - 2 = 2 \)
- The inequality becomes \( 2 \geq 2 \), which is true.

Since both inequalities are true, the point \((2, 2)\) does satisfy both inequalities.

### Checking Point \((0, 3)\)
For the inequalities:
1. \( 3 > -3(0) + 3 \)
- Calculate the right side: \( -3(0) + 3 = 0 + 3 = 3 \)
- The inequality becomes \( 3 > 3 \), which is false.

2. \( 3 \geq 2(0) - 2 \)
- Calculate the right side: \( 2(0) - 2 = 0 - 2 = -2 \)
- The inequality becomes \( 3 \geq -2 \), which is true.

Since the first inequality is false, the point \((0, 3)\) does not satisfy both inequalities.

### Summary
Only the point \((2, 2)\) satisfies both inequalities. The results for each point are:
- \((1, 0)\): false
- \((-1, 1)\): false
- \((2, 2)\): true
- \((0, 3)\): false

So, the final results are:
[tex]\[ [False, False, True, False] \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.